Pembelajaran Membaca Al-Qur’an DenganMetode Ummi - Yazidul Busthomi; Jazirotul Mukaromah; Syamsul A’dlom (STIT Muhammadiyah Paciran Lamongan, 2020)
Pembelajaran Membaca Al-Qur’an DenganMetode UmmiVolume 6No. 2, 1 September 2020209Pembelajaran Membaca Al-Qur’an DenganMetode UmmiYazidul Busthomi,Syamsul A’dlom, danJazirotul MukaromahInstitut Agama Islam Al-Qolam Gondanglegi Malang, IndonesiaEmail: busthomi@alqolam.ac.id, Email: samsuladlom06@gmail.comAbstract: Al-Qur'an is the holy book for Muslim religions throughout the world. As an eternal scripture, also as a guide for all mankind. Whoever speaks based on the Qur'an, then he is speaking the truth. So whoever turns away from the Qur'an, and moves on to other directions, of course, is completely lost. learning to read the al-Qur'an is a process of interaction between educators and students in an activity of arranging letters or words by seeing, recognizing and understanding the life guidelines, namely al-Qur'an to obtain information contained in writing so that it provides benefits for students. The ummi method is one of the lessons compiled by Ustadz Masruri and Ustadz Ahmad Yusuf, a consortant of Islamic education (KPI). This method emphasizes the quality possessed by ustadz and ustadzah, through a learning process that is easy, fun and touching. The ummi method is a system consisting of 3 system components, namely a practical book on the ummi method, quality management of the ummi method, and certified teachers of the ummi method. All three must be used simultaneously if you want to get optimal results from this method